2021
DOI: 10.24251/hicss.2021.019
|View full text |Cite
|
Sign up to set email alerts
|

Design Foundations for AI Assisted Decision Making: A Self Determination Theory Approach

Abstract: Progress of technology and processing power has enabled the advent of sophisticated technology including Artificial Intelligence (AI) agents. AI agents have penetrated society in many forms including conversation agents or chatbots. As these chatbots have a social component to them, is it critical to evaluate the social aspects of their design and its impact on user outcomes. This study employs Social Determination Theory to examine the effect of the three motivational needs on user interaction outcome variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Nonetheless, the potential role of the BPN has been largely neglected in AI research and development. With the current study, we aimed to complement the limited literature on the role of BPN for technology acceptance ( Nguyen and Sidorova, 2018 ; De Vreede et al, 2021 ; Jiménez-Barreto et al, 2021 ). In particular, we wanted to contribute to a better understanding of how two specific design parameters of AI assistants are related to the fulfillment of BPNs and how this, in turn, affects behavioral intentions to use a system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nonetheless, the potential role of the BPN has been largely neglected in AI research and development. With the current study, we aimed to complement the limited literature on the role of BPN for technology acceptance ( Nguyen and Sidorova, 2018 ; De Vreede et al, 2021 ; Jiménez-Barreto et al, 2021 ). In particular, we wanted to contribute to a better understanding of how two specific design parameters of AI assistants are related to the fulfillment of BPNs and how this, in turn, affects behavioral intentions to use a system.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, empirical research that investigates the role of BPN on AI acceptance is scarce to date. Recently, one of the first studies to draw a link between BPN Fulfillment and AI has investigated chatbot-assisted decision-making ( De Vreede et al, 2021 ). The results revealed that a stronger experience of autonomy, competence and relatedness was indeed associated with higher user satisfaction, which subsequently led to greater engagement with the chatbot.…”
Section: Basic Psychological Needs Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…1 With the recent advancement of AI in various industrial sectors, it has played a significant role in individuals' decision-making by providing extracted insights from big data analytics. 2 In that sense, AI-assisted CDM in healthcare can be defined as the process of choosing among options by interacting with AI technology and its analytic suggestions. However, prior studies have documented mixed effects of AI assistance on clinicians' decisionmaking.…”
Section: Introductionmentioning
confidence: 99%